2006 World Automation Congress 2006
DOI: 10.1109/wac.2006.376028
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Human Leadership Approaches for Role Allocation in Human-Robot Navigation Scenarios

Abstract: In this paper, we propose to examine the practices of leadership defined in human relationships and model their use in maximizing performance for human-robot interaction scenarios. This process involves first defining the human-robot space of interaction and mapping the situational context in which human leadership styles are most fitting. We then determine which behavior, for both the human and robot, is most appropriate in order to understand the proper roles for human-robot integration. From there, we model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…By balancing between the cognitive limits of the operator and the swarm's need for guidance and specific decisions, the researchers were able to control swarms of up to 100 UAVs without an increase in errors or loss of SA. Howard and Cruz (2006) had similar findings in a related experiment where they tested directive (or command) leadership's effectiveness against that of transactional (or reward-based, collaborative) leadership. They also found that operators functioned best when guiding the swarm as part of the team, rather than as a commander, in part because it allowed the operator to focus on a manageable section of the swarm, rather than the entire group.…”
Section: Results Of Individual Studiesmentioning
confidence: 57%
See 1 more Smart Citation
“…By balancing between the cognitive limits of the operator and the swarm's need for guidance and specific decisions, the researchers were able to control swarms of up to 100 UAVs without an increase in errors or loss of SA. Howard and Cruz (2006) had similar findings in a related experiment where they tested directive (or command) leadership's effectiveness against that of transactional (or reward-based, collaborative) leadership. They also found that operators functioned best when guiding the swarm as part of the team, rather than as a commander, in part because it allowed the operator to focus on a manageable section of the swarm, rather than the entire group.…”
Section: Results Of Individual Studiesmentioning
confidence: 57%
“…By using transactional control (incentivizing the swarm into performing a task without commanding each step of taskcompletion process) on swarms with a higher LOA, Howard and Cruz (2006) showed that swarms could achieve their goal with fewer errors and lower cognitive workload for the operator. Kira and Potter (2009) corroborated these findings in a scenario requiring the swarm to split up while defending a point and pursuing an attacker.…”
Section: Using Multiple Swarm Management Approachesmentioning
confidence: 99%
“…The theory states that humans adjust to technology and, similarly, technology should adapt to humans. Following this theory and the work of [8], we can justify an attempt to apply leadership styles developed for human organisations to the human-robot interaction space. It is hoped that the wellunderstood nature of these leadership styles and the familiarity of their application will resonate with human operators and lead to a greater level of comfort and acceptance in hybrid human/robot teams.…”
Section: Leadership Styles For Human Teamsmentioning
confidence: 99%
“…Perhaps the complement of this application of computer science to humans is [8] where human leadership paradigms are examined for relevance to the case where the team's leader is leading a single robot. In this work, the authors collect common statements of human leadership styles from [12] [14][3] and attempt to remove reference to human traits such as personality, reducing the style to a set of concepts which can be implemented in a robot control interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation